2012
DOI: 10.1111/j.1476-5381.2011.01381.x
|View full text |Cite
|
Sign up to set email alerts
|

A new cannabinoid CB2 receptor agonist HU‐910 attenuates oxidative stress, inflammation and cell death associated with hepatic ischaemia/reperfusion injury

Abstract: BACKGROUND AND PURPOSECannabinoid CB2 receptor activation has been reported to attenuate myocardial, cerebral and hepatic ischaemia-reperfusion (I/R) injury. EXPERIMENTAL APPROACHWe have investigated the effects of a novel CB2 receptor agonist ((1S,4R)-2-(2,6-dimethoxy-4-(2-methyloctan-2-yl)phenyl)-7,7-dimethylbicyclo[2.2.1]hept-2-en-1-yl)methanol (HU-910) on liver injury induced by 1 h of ischaemia followed by 2, 6 or 24 h of reperfusion, using a well-established mouse model of segmental hepatic I/R. KEY RESU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(96 citation statements)
references
References 37 publications
(77 reference statements)
3
89
0
3
Order By: Relevance
“…Activation of hepatic CB 1 receptors by endocannabinoids or synthetic ligands promotes alcoholic- (Jeong et al, 2008) and non-alcoholic steatohepatitis (Osei-Hyiaman et al, 2005;Tam et al, 2012), liver injury (Horvath et al, 2012a;Cao et al, 2013) and fibrosis (Teixeira-Clerc et al, 2006). In contrast, CB 2 receptor activation has tissue protective, anti-inflammatory and antifibrotic effects in preclinical models of liver injury, inflammation and fibrosis (Batkai et al, 2007;Teixeira-Clerc et al, 2010;Louvet et al, 2011;Horvath et al, 2012a;Cao et al, 2013). However, despite the promise of selective CB 2 receptor agonists in liver disease based on preclinical studies, no such agonists are available suitable for human testing in liver disease to date.…”
mentioning
confidence: 99%
“…Activation of hepatic CB 1 receptors by endocannabinoids or synthetic ligands promotes alcoholic- (Jeong et al, 2008) and non-alcoholic steatohepatitis (Osei-Hyiaman et al, 2005;Tam et al, 2012), liver injury (Horvath et al, 2012a;Cao et al, 2013) and fibrosis (Teixeira-Clerc et al, 2006). In contrast, CB 2 receptor activation has tissue protective, anti-inflammatory and antifibrotic effects in preclinical models of liver injury, inflammation and fibrosis (Batkai et al, 2007;Teixeira-Clerc et al, 2010;Louvet et al, 2011;Horvath et al, 2012a;Cao et al, 2013). However, despite the promise of selective CB 2 receptor agonists in liver disease based on preclinical studies, no such agonists are available suitable for human testing in liver disease to date.…”
mentioning
confidence: 99%
“…Of interest, the CB1 receptor in the liver has been shown to mediate profibrogenic effects (Teixeira-Clerc et al, 2006) and has also been implicated in the pathogenesis of alcoholic and nonalcoholic liver disease (Hé zode et al, 2008;Jeong et al, 2008). On the other hand, CB2 receptor agonism shows opposite antifibrogenic and anti-inflammatory effects in hepatic and nonhepatic tissue (Muñ oz-Luque et al, 2008;Akhmetshina et al, 2009) and protects against liver ischemia-reperfusion injury (Horvá th et al, 2011). Previous studies by our laboratory have demonstrated that the proangiogenic peptide, apelin (AP), is up-regulated in HSCs of patients with cirrhosis (Melgar-Lesmes et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, selective activation of CB2 receptor in endothelium and/or leukocytes suppresses their interaction and protects the BBB (177,195). Similarly, CB2 activation also attenuates the proinflammatory response in human coronary and hepatic endothelial cells (9,97,188).…”
Section: Biosynthesis and Receptors Of Endocannabinoids In Cells Invomentioning
confidence: 99%
“…Cannabinoids were shown to inhibit the production of TNF-␣ and other cytokines in LPS-stimulated microglial and cerebellar granule cells (61,186), and in one study CB2 receptors were implicated to mediate this effect (196). CB2 activation was also reported to attenuate TNF-␣-induced proinflammatory responses in human coronary endothelial cells (9,97,188). A similar interaction between TNF-␣ and endocannabinoids or synthetic CB2 agonists could potentially attenuate delayed cerebrovascular constriction and consequent brain ischemia after SAH, since TNF-␣ has been reported recently to play a significant pathogenic role in this process by enhancing the myogenic tone in cerebral arteries, resulting in the development of vasospasm (256).…”
Section: Translational Perspectivesmentioning
confidence: 99%